2018
DOI: 10.1681/asn.2017111218
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuins in Renal Health and Disease

Abstract: Sirtuins belong to an evolutionarily conserved family of NAD-dependent deacetylases that share multiple cellular functions related to proliferation, DNA repair, mitochondrial energy homeostasis, and antioxidant activity. Mammalians express seven sirtuins (SIRT1-7) that are localized in different subcellular compartments. Changes in sirtuin expression are critical in several diseases, including metabolic syndrome, diabetes, cancer, and aging. In the kidney, the most widely studied sirtuin is SIRT1, which exerts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
208
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(212 citation statements)
references
References 130 publications
3
208
0
1
Order By: Relevance
“…Sirtuins belong to the family of conserved nicotinamide adenine dinucleotide-(NAD + -) dependent deacetylases and are involved in stress response, cell proliferation, and antiapoptosis processes [6]. Sirtuin-3 (Sirt3) is localized mainly in the mitochondrial matrix [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sirtuins belong to the family of conserved nicotinamide adenine dinucleotide-(NAD + -) dependent deacetylases and are involved in stress response, cell proliferation, and antiapoptosis processes [6]. Sirtuin-3 (Sirt3) is localized mainly in the mitochondrial matrix [6].…”
Section: Introductionmentioning
confidence: 99%
“…Sirtuins belong to the family of conserved nicotinamide adenine dinucleotide-(NAD + -) dependent deacetylases and are involved in stress response, cell proliferation, and antiapoptosis processes [6]. Sirtuin-3 (Sirt3) is localized mainly in the mitochondrial matrix [6]. It plays a pivotal role in maintaining mitochondrial function, protecting against oxidative stress-induced damage by deacetylating lysine residues of mitochondrial proteins, and maintaining the kidney function [7].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies have shown that SIRT1 possesses the ability to inhibit inflammatory response . In the present study, we detected the expression of SIRT1 in TiPs‐treated animal models and macrophages.…”
Section: Resultsmentioning
confidence: 69%
“…Recently, studies have shown that SIRT1 possesses the ability to inhibit inflammatory response. [27][28][29][30] In the present study, we detected the expression of SIRT1 in TiPs-treated animal models and macrophages. As shown in Figure 5A,B, the protein level of SIRT1 was markedly decreased by TiPs compared to the Sham group.…”
Section: Sirt1 Was Downregulated By Tips In Vivo and In Vitromentioning
confidence: 77%
“…Concurrently, and in accordance with previous studies showing that knockout or inhibition of RAGE prevented CML‐ or LPS‐induced reduction in SIRT1 expression (Grossin et al, ; Huang et al, ), SIRT1 expression was here downregulated in old WT compared with old RAGE −/− mice. Interestingly, reduced renal inflammation and fibrosis have been reported in genetic or pharmacological boosting of SIRT1 models (Hong et al, ; Morigi, Perico, & Benigni, ); on the other hand, its deletion was associated with an aggravation of kidney injuries such as GS (Chuang et al, ). Together, these results suggest a potentially major role for SIRT1 in renal aging.…”
Section: Discussionmentioning
confidence: 99%